2018
DOI: 10.7759/cureus.3199
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Depression Among Patients of Myocardial Infarction in Karachi, Pakistan: A Cross-sectional Study

Abstract: BackgroundDepression is a well-known risk factor that aggravates the chances of having various complications of acute coronary syndrome (ACS) such as cardiovascular collapse, heart failure, arrhythmia, recurrent myocardial infarction, and stroke among patients of ACS. ACS is a broad term which includes unstable angina as well as myocardial infarction (MI). The purpose of this study is to analyze the prevalence of depression among the patients of MI admitted to the tertiary care hospitals of Karachi, Pakistan.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Numerous studies have shown that patients with CAD and depression have poor health outcomes. 3 Depression in different aspects in Pakistani population after myocardial infarction, 4 after PCI 5 and in inhospital patients with CAD 6 were evaluated and found to have significant mental illness which co-relates with the results of other international studies.…”
mentioning
confidence: 62%
“…Numerous studies have shown that patients with CAD and depression have poor health outcomes. 3 Depression in different aspects in Pakistani population after myocardial infarction, 4 after PCI 5 and in inhospital patients with CAD 6 were evaluated and found to have significant mental illness which co-relates with the results of other international studies.…”
mentioning
confidence: 62%
“…Of these records, 28 studies met our inclusion/exclusion criteria and were included in the final meta-analysis. [20–47] The most common reason for exclusion of a study following full-text review was ACS diagnostic criteria were not provided. A total of 4699 patients were ACS depression patients.…”
Section: Resultsmentioning
confidence: 99%